Survival endpoints for young women with early stage uterine endometrioid carcinoma: a matched analysis. (December 2016) - Isrow, Derek; Burmeister, Charlotte; Hanna, Rabbie K.; Elshaikh, Mohamed A.
Abstract: Objectives: Younger age is thought to be a favorable prognostic factor in women with endometrial carcinoma (EC). Survival endpoints were compared between two matched groups of patients with early stage EC: women 45 years or younger and women older than 45 years. Methods and materials: Two matched groups of patients were created based on stage, grade, lymph node dissection and adjuvant management. Recurrence-free (RFS), disease-specific (DSS) and overall survival (OS) were calculated. Results: A total of 525 patients (88 younger patients and 437 older patients, matched 1:5) were included in this study. The two groups were well balanced except for less myometrial invasion in the younger patients. There were no significant differences between younger and older patients in regards to 5-year RFS (94% vs. 91%, p = 0.6902). Similarly, there was no significant difference in regards to DSS (96% vs. 97%, p = 0.9000). While 5-year OS was similar for both groups (89% vs. 89%, p = 0.9942), 10-year OS was longer in the younger group (83% vs. 68% with p = 0.13). On multivariate analysis for RFS, the presence of lymphovascular space invasion was the only predictor of shorter RFS (p = 0.0007). Tumor grade (p = 0.0002) and lower uterine segment involvement (p = 0.0141) were independent predictors of shorter DSS. Older age (p < 0.001) and stage II (p = 0.01) were the only predictors of shorter OS. Conclusions: When matched based on tumor stage, grade and adjuvant management, our study suggests that there is no difference in survival endpoints between younger and older patients with early stage endometrial carcinoma.